Notes on the moray eels (Anguilliformes: Muraenidae) of Malaysia with two new records - Kar, Hoe Loh; Muhammad Ali Syed Hussein; Ving, Ching Chong; A. Sasekumar (Universiti Kebangsaan Malaysia, 2015)
Two new records of moray eels (Muraenidae), Gymnothorax margaritophorus Bleeker, 1864 and Strophidon sathete (Hamilton 1822), are reported for Malaysia. They are represented by two specimens each, all collected from Sabah waters. The present study also provides the current taxonomic and distributional information of the Malaysian moray eels. To date, there are 33 species belonging to six genera of the Muraenidae in Malaysian waters based on the published records.